AB0253 To What Extent is Foot Pain Attributable to Disease Activity in RA Patients?. (9th June 2015) - Hernandez-Flόrez, D.; González-Fernández, M.L.; Valor, L.; Morales Lozano, M.R.; Martínez, J.; del Río, T.; Nieto, J.C.; Janta, I.; Lopez Longo, F.J.; González, C.; Monteagudo, I.; Martínez-Estupiñán, L.; et al.
Abstract : Background: A high prevalence of foot pain (70-90%) has been widely described in rheumatoid arthritis (RA) (1-4). Foot inflammation in RA usually starts in the metarsophalangeal (MTP) joints, extends to other joints with consequent pain, deformities and functional impairment (5, 6). The foot disorders and complaints it might have their origins in inflammatory disease activity or biomechanical abnormalities. Objectives: The objective of this cross-sectional prospective study was to establish what extend foot complaints in RA patients in remission or low disease activity may originate in subclinical inflammatory disease activity as opposed to podiatric biomechanical abnormalities. Methods: We recruited 136 patients with foot complaints. Sixty-two were bDMARD-treated RA patients presenting DAS-determined remission or low disease activity while the remaining 74 were gender matched controls without rheumatic or muskoskeletal disorders. In an effort to identify the root cause of pain, we subjected both groups to a comprehensive podiatric and biomechanical assessment followed by an ultrasound (US) scan. Results: Most RA patients and controls were female (77.4% and 83.8%, respectively). There was no statistical difference in the proportion of obese subjects in either group (p=0.792). Inappropriate shoes were used by 50.0% of RA patients and 33.8% of controls (p=0.080). Talalgia, particularly heel pain, was more frequent in the control group, with associated talalgia and metatarsalgia being more prevalent in the RA group (p<0.05). The RA patient group was also more likely to present greater foot deformity, more limited joint movement and foot pathologies than the controls. US inflammatory and structural changes were significantly more frequent in RA patients than in controls (p<0.05). US structural involvement was significantly associated with limited joint mobility and pathologic biomechanical tests only in RA patients (p<0.05). Conclusions: RA foot pathologies often seem to be linked to disease activity and ultrasound can be useful to help the clinician differentiate disease-related foot pain from other possible biomechanical causes. References: Hooper L, et al. Arthritis Care Res.2012;64(8):1116-24. Rome K, et al. J Foot Ankle Res.2009;2:16. Rao S, Best Pract Res Clin Rheumatol 2012;26(3):345-68. Fuchs HA, et al. Arthritis Rheumatol.1989;32(5):531-7. van der Leeden M, et al. Rheumatology.2006;45(4):465-9. van der Leeden M, et al. Arthritis Res Ther.2010;12(1):R3. Disclosure of Interest: None declared